Ruins of the present through contemporary photography - Gurieva, N.; Cecilia Alondra Perez Aguilera (ТОВ «Друкарня Мадрид», 2024)
The past, like the future, is not a time before and after in relation to the present, but simply projections of the present, carried out in accordance with special rules. When it is possible to extend the concept of ruins to objects of the modern era, the distance between the past and the present is destroyed, the very structure of time crumbles.
Keywords: present; contemporary photography